Innovation and Entrepreneurship for Supply Chain Management & Logistics - Michael Kloep (International Journal of Supply Chain Management, 2020)
Abstract- This paper provides a review of the relevant factors for achieving performance as an entrepreneur in the position of supply chain manager. Findings from recent literature suggests that at least five factors play a major role entrepreneurial supply chain management competence, namely innovation orientation, risk-taking characteristics, pro-activeness orientation, relational capital, and coordination capability. Several potential causes of business failure are also identified, including lack of planification and problems with the suppliers.  A careful consideration of the practical implications of these findings may help supply chain managers improve the performance of their business.